PENINGKATAN PERTUMBUHAN BIBIT TANAMAN KARET (Hevea brasiliensis, Müll.Ar) MELALUI APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT PADA MEDIA TANAM - Charlos Togi Stevanus; Jamin Saputra (University of Prof. Dr. Hazairin, SH, 2020)
Oil palm empty bunches (TKKS) are one of the largest solid waste palm oil processing which has the potential as raw material for compost to increase the growth of rubber plant material. The purpose of this study was to determine the effect of TKKS compost applications on the growth of rubber plant material and the reduction of inorganic fertilizers. The study using a randomized block design (RBD) consisting of 6 treatment combination of compost and reduction of inorganic fertilizers namely : 1) control (without compost and fertilizer); 2) 100 % general dosage (DU) of inorganic fertilizer; 3) 1.000 gram compost; 4) 800 gram compost + 25 % DU; 5) 600 gram + 50 % DU compost; and 6) 400 gram compost + 75 % DU. The results show that a combination of TKKS compost and inorganic fertilizer were not significantly different to increase plant growth. A Significant difference was shown in the parameter of grafting successfully by use of 400 – 600-gram compost TKKS accompanied by a reduction of 25-50 % inorganic fertilizer in planting media. In addition, TKKS compost also has tendency to increase the nutrient content of K, Ca, and Mg compared to without compost application.